Duplex realtime PCR method for Epstein-Barr virus and human DNA quantification: its application for post-transplant lymphoproliferative disorders detection - Fellner, María Dolores (2014)
Fil: Fellner, María Dolores. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.